The Delimitation of Bipolar Metropolitan Area within the Kujawsko-Pomorskie Region - Miroslaw Biczkowski; Iwona Muller-Fraczek; Joanna Muszynska; Michal Bernard Pietrzak; Justyna Wilk (Institute of Economic Research (IER), 2014)
The objective of the article was to re-define the bipolar metropolitan area within the Kujawsko-Pomorskie region (NUTS 2). Concentration of metropolitan features, as well as socio-economic situations of its communes (NUTS 5) in 2011, and also their development in the period 2009-2011 were examined. Bydgoszcz and Torun, the economically strongest cities in the region, were established as the dual core of the metropolitan area. The determined metropolitan area will cover the most developed communes which meet the following criteria: neighbourhood, continuity, compactness, maximum distance and population. The development levels of communes were determined using taxonomic development measure. Its values were calculated considering the economic and also social aspects of regional development, as well as features typical of metropolitan areas, such as: well-developed sectors of R&D, knowledge-based economy and serving superior services. The metropolitan area resulted from the research slightly differs from the Bydgoszcz-Torun Metropolitan Area (appointed in 2005) and composed all of the communes located within the Bydgoski and Torunski districts (NUTS 4). Chelmza and Koronowo, the less developed communes of the districts, were excluded from the new metropolitan area, while the neighbouring communes of Ciechocinek, Naklo and Unislaw were included due to their significant level of regional development. The Inowroclaw district is a prospective candidate to join the metropolitan area.
Keywords: C38; O1; R11; 330; delimitation; metropolitan area; synthetic measure of development